Productivity improvements at small manufacturing company’s shop-floor - Asafu-Adjaye, George Gray Adonteng (My University, 2011)
An effort to increase and improve the productivity has been started by the case company at which this thesis was conducted. Various productivity measures and improvements are being currently being studied to achieve a leaner production and easy material flow. In productivity improvements the ultimate goal is to seek out new production manufacturing processes that can increase the company’s overall efficiency in order to stay competitive in the market. This could be accomplished by the reduction or total elimination of losses that occur mechanically or through a bad operational process. The aim of this thesis is to develop a simple productivity measuring of the manufacturing machine and also to make a bidding calculator or sales tool to be used to speed the rate at which they set bids. By using literature from previous studies, unstructured interviews of managers, supervisors and employees the tasks to be performed were set. A recording sheet was created to record the rate at which the machines at the shop-floor were being utilized and this study we named as machine hour study. This study is to help us to understand the current state of utilization so as to figure out measures to increase the productivity. The second task was to modify the bidding calculator or sales tool to be more user-friendly. Lastly, the author was to recommend other projects that could help in the improvement of productivity at the shop-floor. The significant result is the fact that the machines being used in manufacturing were being underutilized which was agreed by the supervising managers at the shop-floor. Some of the reasons pertaining to this result are too much setup in a working day, long searchers for tools, not enough work, etc.
Keywords: Productivity; set-up; shop-floor; bidding process; fi=Master's Degree Programme in Industrial Management|